Augmented Reality in Primary Science Education: A Systematic Development Study Using Assemblr Edu Platform - Zantika Zulmi; Nurul Fitriah Aras; Sinta Satria Dewi Pendit; Abdul Rahman; Ryan Andika Pratama (Papanda Publisher, 2026)
Conventional science instruction in Indonesian elementary schools often fails to adequately engage students, particularly when teaching complex anatomical concepts requiring three-dimensional visualization. This study developed and evaluated Assemblr Edu-based Augmented Reality (AR) learning media for the five senses topic in fourth-grade science education. Employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the research was conducted at Karuna Dipa Elementary School, Palu, involving 16 fourth-grade students. Expert validation assessed media validity through structured questionnaires. Practicality was evaluated via user response questionnaires from six students and one teacher. Effectiveness was measured through pre-test/post-test design with Normalized Gain (N-Gain) analysis. Expert validation yielded exceptional validity scores: material expert (99.3%) and media expert (91.6%), with a combined average of 95.45%. User practicality assessments showed high scores from students (90.41%) and teacher (92.5%). Learning outcomes demonstrated substantial improvement, with average pre-test scores of 65.3% increasing to 94% post-test, resulting in an N-Gain of 0.827, categorized as high effectiveness. The Assemblr Edu-based AR media proved highly valid, practical, and effective for enhancing elementary students' science learning outcomes. The systematic ADDIE-guided development process produced instructional media that significantly improved student engagement and conceptual understanding, providing a replicable model for integrating immersive technologies in resource-constrained educational contexts.